1998
DOI: 10.1021/ja981216s
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Diiron Centers of Non-Heme Iron Enzymes. Preparation of Sterically Hindered Diiron(II) Tetracarboxylate Complexes and Their Reactions with Dioxygen

Abstract: A series of diiron(II) complexes, [Fe 2 (µ-L)(µ-O 2 CR)(O 2 CR)(N) 2 ], where L is a dinucleating bis-(carboxylate) ligand based on m-xylylenediamine bis(Kemp's triacid imide) and N is a pyridine-or imidazolederived ligand, were prepared as models for the carboxylate-bridged non-heme diiron cores of the O 2 -activating enzymes, soluble methane monooxygenase hydroxylase (MMOH), and the R2 subunit of ribonucleotide reductase (RNR-R2). X-ray crystallographic studies revealed differences in the coordination geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
85
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 39 publications
13
85
1
Order By: Relevance
“…The shift of the carboxylate coordination mode from monodentate in 4 to syn-syn bidentate bridging in 2 and 3 and to the chelating in 5 implied largely the influence of basicity of the lone pair on the carbonyl oxygen of the carboxylate moiety and sterics. Such 'carboxylate shift' process has important implications for metalloenzymes in understanding their catalytic activities [51][52][53][54]. …”
Section: Molecular and Crystal Structuresmentioning
confidence: 99%
“…The shift of the carboxylate coordination mode from monodentate in 4 to syn-syn bidentate bridging in 2 and 3 and to the chelating in 5 implied largely the influence of basicity of the lone pair on the carbonyl oxygen of the carboxylate moiety and sterics. Such 'carboxylate shift' process has important implications for metalloenzymes in understanding their catalytic activities [51][52][53][54]. …”
Section: Molecular and Crystal Structuresmentioning
confidence: 99%
“…The XDK 2− ligand also supports carboxylate-bridged diiron(II) units having the general composition [Fe II 2 (XDK)(μ-RCO 2 )(RCO 2 )( N -donor) 2 ], where R = t -Bu- (pivalate), PhCy- (1-phenylcyclohexylcarboxylate), Ph- (benzoate), i Pr- (isobutyrate), or t BuCH 2 - (1- tert -butylacetate); N -donor = py (pyridine), 3-Fpy (3-fluoropyridine), N -MeIm ( N -methylimidazole), or N - t BuIm ( N - tert -butylimidazole) [5456]. More sterically hindered XDK 2− variants, containing either propyl (PXDK 2− ) or benzyl (BXDK 2− )in place of methyl substituents on the Kemp’s triacid moiety, could also be employed to assemble similar diiron(II) compounds.…”
Section: Ligand Platformsmentioning
confidence: 99%
“…More sterically hindered XDK 2− variants, containing either propyl (PXDK 2− ) or benzyl (BXDK 2− )in place of methyl substituents on the Kemp’s triacid moiety, could also be employed to assemble similar diiron(II) compounds. The asymmetric bridging mode of the ancillary carboxylate to the diiron(II) core is determined by both steric and electronic factors [56]. X-ray structural studies suggested that greater steric repulsion between XDK 2− and the external carboxylate, and more basic N -donors, favor a syn,syn -bidentate bridging mode of the ancillary carboxylate rather than a syn,anti -monodentate one.…”
Section: Ligand Platformsmentioning
confidence: 99%
“…Kemp's triacid was used for selective recognition studies of carboxylate anions [6][7][8][9] and its some imide derivatives (m-xylenediamine bis(Kemp's triacid imide) as complexones of divalent metal cations such as Zn 2+ , Co 2+ , Mg 2+ [10][11][12][13][14][15][16][17][18]. KTA complexes with Fe +2 were used as models of non-heme iron enzymes [19] and as a porphyrin-linked dicarboxylate ligand in tri-iron complexes [20]. Condensation of Kemp's triacid with aromatic diamines has given new type of ionophore selective toward Hg +2 cations [21].…”
Section: Introductionmentioning
confidence: 99%